KKN Tematik Penerapan Teknologi Dalam Rangka Mendukung Percepatan Pemulihan Ekonomi Pedesaan - Mulyani, Asri; Faisal, Ridwan Nur; Sopian, Alpi; Nuraisah, Tintin; Prayoga, Hardi; Alamsyah, Fathi Ridwan; Firdaus, Raden Syaban; Aulia, Wafa Gaida; Ramdhani, Nabila Aprilia; Suwandy, Mochamad Riefky Rafliana; Ardimansyah, Dendi; Gumelar, Agung; Ruspa, Rena; Mustaatinah, Tutin; Aldiansah, Aldiansah; Oktavian, Gilang Anhari; Arifin, Pipin Zaenal; Banowati, Rika; Andarista, Hilda Dian (Institut Teknologi Garut, 2023)
Real Work Lecture is a mandatory activity that combines the implementation of the Tri Dharma of Higher Education with the method of providing learning and work experience to students. KKN is also a vehicle for the application and development of science and technology which is carried out outside the campus within certain times, work mechanisms, and requirements. The real work lecture that has been held in Sindangprabu Village, Wanaraja District, Garut Regency, West Java during August 2022, with this Thematic Real Work Lecture is expected to help with the difficulties faced by the government, including in handling the development of villages in the Wanaraja sub-district, district Garut in an effort to increase the Human Development Index (IPM) of Garut and West Java. In general, the shift in the economic structure that occurred in Garut and West Java districts looks the same, namely the shift from the primary sector to the secondary and tertiary. Garut's condition only relies on the agricultural sector, of course the economy so that, on its way to the industrialization transition area, Garut district really needs to build a foundation a strong economy, including creating human resources to increase village potential and independent industrial commodities or industries that make better use of domestic resources than imports.